CELLULOSIC PADS AS MATRIX SACHET ANTIMICROBIAL: A REVIEW - Syifa Robbani; Farah Fahma; Sugiarto Sugiarto (AGROINTEK, 2021)
The advancement of active packaging technology has contributed to the need for customer assurance of the quality and protection of fresh foods and agricultural products. An example of active packaging to maintain food quality and improve product protection is the use of antimicrobial pads. Antimicrobial pads are a type of active packaging that releases active agents into the headspace food packaging in order to prevent, inhibit or destroy the growth of microorganisms.. Antimicrobial pads are very easy to apply to food products by placing them on the bottom of the product or inserting them into the packaging material. This literature study discusses the characterization of cellulose as a major component in the manufacture of pads, techniques for the incorporation of antimicrobial compounds into pads, and suitable applications for the inhibition of microorganisms in food products. Apart from that, this literature study also discusses the advantages and disadvantages of antimicrobial pads as active packs.